The Dark Tetrad and Male Clients of Female Sex Work - Davis, Adam C.; Vaillancourt, Tracy; Arnocky, Steven (Frontiers in Psychology, 2020)
Many scholars have investigated the attitudes, beliefs, motives, and behavior of male clients of female sex workers. However, few have examined individual differences in major dimensions of personality expressed by men who purchase prostitution compared to those who do not. Although several evolutionary psychologists have studied prostitution and those involved in sex work, to our knowledge, none have explicitly considered the utility of an evolutionary personality perspective in trying to understand why particular men pay for sex. In the current mini-review, following other researchers, prostitution is described principally as a form of short-term mating sought primarily by men. We argue that the socially aversive traits embodying the Dark Tetrad (narcissism, Machiavellianism, psychopathy, and sadism) may characterize certain male clients of female sex workers, particularly those consumers expressing the motives of desiring exciting and novel sex with women who are treated with contempt, perceiving prostitution in a business-like manner with little emotional involvement, and seeking to dominate and control sex workers who are viewed as vulnerable and subservient. The traits of the tetrad may also be more prevalent among men who purchase sex from female sex workers in outdoor (e.g., street prostitution) in comparison to indoor settings (e.g., escort agencies).